154k views
1 vote
What is (2x-3y) (4x-y)

User Ken Ma
by
5.0k points

2 Answers

4 votes
8x²-2xy-12xy+3y²

8x²+3y²-14xy

User SanjiMika
by
4.8k points
2 votes

ANSWER


(2x-3y) (4x-y) = 8 {x}^(2) -14xy + 3 {y}^(2)

Step-by-step explanation

We want to expand (2x-3y) (4x-y)

We use the distributive property to obtain,


(2x-3y) (4x-y) = 2x(4x-y) -3y(4x-y)

We expand to get,


(2x-3y) (4x-y) = 8 {x}^(2) -2xy -12xy + 3 {y}^(2)

Combine the middle terms to obtain,


(2x-3y) (4x-y) = 8 {x}^(2) -14xy + 3 {y}^(2)

User Leon Vismer
by
5.4k points